2022
DOI: 10.3390/atmos13111751
|View full text |Cite
|
Sign up to set email alerts
|

Using Long-Term Historical Meteorological Data for Climate Change Analysis in the Carpathian Region

Abstract: In this study, we consider the historical climatological time series available in the meteorological yearbooks of the Royal Hungarian Central Institute of Meteorology and Earth Magnetism, first published in 1871. Data quality improvement of historical data includes the homogenization process with outlier checks and data gap filling by applying the MASH software. We investigated 13 stations from the Carpathian Region having the most complete monthly temperature and precipitation time series for the period of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The series is homogeneous and the verification was completed with the von Neumann test [44]. To check the homogeneity, MASH v3.03 software can also be used, which was successfully applied in the area of the Pannonian basin [45].…”
Section: Methodsmentioning
confidence: 99%
“…The series is homogeneous and the verification was completed with the von Neumann test [44]. To check the homogeneity, MASH v3.03 software can also be used, which was successfully applied in the area of the Pannonian basin [45].…”
Section: Methodsmentioning
confidence: 99%
“…An earlier study by Domonkos [55] already detected a significant drop of annual precipitation totals in the 20th century based on aggregated monthly data. Ilona et al [51] also revealed significant changes in the aggregated values of precipitation by comparing historical (1871-1918) and recent (1971-2020) periods. At lowlands, the drop in precipitation totals is larger than 20% during spring and autumn seasons.…”
Section: Precipitation Trendsmentioning
confidence: 96%
“…A shift in the distributions is observed only at a few stations. Note that significant trends were not really detected either in the historical data or in recent decades; the latter is somewhat surprising [51]. Lakatos et al [56] analyzed sub-daily precipitation statistics in the region.…”
Section: Precipitation Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…So with MASH, we have a temporally representative database, but not yet a spatially representative database (Ilona et al, 2022; Izsák et al, 2022; Venema et al, 2012). So the next step is to ensure spatial representativity: we interpolate the values to a dense regular grid network and can then report on the climate and its possible changes over the whole country.…”
Section: Interpolation Of Relative Humidity Hourly Datamentioning
confidence: 99%